Elastic system of the rat ventral prostate and its modifications following orchiectomy - deCarvalho, H. F.; Vilamaior, PSL; Taboga, SR (Wiley-Blackwell, 1997)
BACKGROUND. The extracellular matrix (ECM) has important roles in prostatic development, and marked stromal changes take place in the rat ventral prostate (VP) after androgen deprivation. However, little knowledge exists about individual ECM components.METHODS. The distribution of elastic fibers (EF) and elastic-related fibers (ERF) in the VP of castrated and control rats was investigated, using histochemistry and transmission electron microscopy (TEM).RESULTS. EF are barely detected in the prostatic stroma, but ERF are relatively abundant. Castration results in a relative increase in the number and thickness of ERF. TEM showed an open network of ECM microfibrils throughout the stroma and thin and short EF, which increase in number and thickness after orchiectomy.CONCLUSIONS. The presence of elastic system components in the rat VP warrants the deformability required for the secretion exclusion under the action of smooth muscle cells, and the castration-induced modification may be related to the contraction of the tissue and maintenance of peculiar arrangements of other ECM components. (C) 1997 Wiley-Liss, Inc.
Keywords: prostate; elastin; microfibrils; elastic-related fibers; castration